Курсы дополнительного профессионального образования для студентов-выпускников как залог успешной деятельности молодого учителя - Абенова, Ю.С. (My University, 2016)
Our century makes an order for the graduates of pedagogical institutes, which can have probabilistic thinking, so they can oriented in unknown situations. Therefore, now it is necessary to include new pedagogical technologies in the educational process, which should supply individualization of education and they will create pupils’ independency.
Keywords: educational technologies; educational methods; education in groups; the teaching of history; activity of the young teacher